Pediatrics - Brown, Lloyd J.; Coller, Ryan; Miller, Lee T. (Lee Todd) (Philadelphia : Wolters Kluwer, 2019)
BRS Pediatrics is a comprehensive review of general and subspecialty pediatrics aimed for medical students on their core clerkship in pediatrics. Written in the popular Board Review Series outline format, this text presents the essentials of pediatrics through concise descriptions, clinical correlations, numerous figures and nearly 100 tables. This revision will include over 500 board-style questions with complete answers and explanations, with exams at the end of each chapter and an end-of-book Comprehensive Examination.
Includes index.
Keywords: Pediatrics -- Examinations, questions, etc; Pediatrics